The Effectivity of Environmental Education in Scaffolding Students’ Ecological Literacy - Ikhsan, F. A.; Kurnianto, F. A.; Apriyanto, B.; Nurdin, E. A. (Jurnal Pendidikan IPA Indonesia, 2019)
This study aimed to determine the effectiveness of environmental education as an effort to scaffold students’ ecological literacy to bring about a sustainable society. The survey method was applied in this research. This research was conducted at the Faculty of Teacher Training and Education of Jember University, which involved the heads of the study program, lecturers, staffs, and students. Data analysis was done descriptively for both dependent and independent variables by using a non-parametric statistic test. The results showed that there was a significant favorable influence of faculty policy, curriculum implementation, instructional method, and campus culture toward the students’ ecological literacy through environmental education, as marked by significance level of 0.00 < 0.05. The research findings evinced that the four components could escalate the students’ ecological literacy on an on-going basis, concerning internalization of theory, real-life application, and scientific thinking through Environmental Education (EE).